USE OF TECHNICAL EQUIPMENT AND INFORMATION SUPPORT TO INCREASE THE OBJECTIVENESS OF JUDGING IN SPORTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article discusses issues related to the study of the use of various technical means and equipment to ensure the objectivity of refereeing. Numerous examples of such technical support are given. Technological progress, information and computer technologies have significantly influenced the increase in the objectivity of refereeing. The use of special computing systems, analytical systems, and hardware complexes in certain sports has become a mandatory requirement when holding sports competitions of the appropriate level. The level of technical support for competitive activities, including refereeing, is determined, on the one hand, by technological progress, and, on the other hand, by the specifics of sports. Mostly more complex sports in terms of the volume of game moments, the presence of technical elements and motor actions, require more complex work of judges, which also requires better technical support and the use of measuring equipment.Using a research method such as interviews with leading professional practitioners, it was possible to identify various controversial game situations and competitive moments in certain sports that require referees to make difficult decisions. Among the difficult controversial moments during refereeing, the following were identified: double touching of the ball during an overhead pass in volleyball; fixing the taking of the scoring field with a large number of players in rugby; determining the shuttlecock hitting the field when performing a high-distance hit in badminton; determining the athlete who was the first to go outside the mat in freestyle wrestling; establishing an error related to changing the starting position during the bench press in powerlifting.The authors of the article proposed a number of ways to improve the objectivity of refereeing through the use of various technical means and measuring equipment. In particular, some technical solutions to improve refereeing were proposed in volleyball, badminton, freestyle wrestling, rugby and powerlifting.
Keywords: technical means; equipment; refereeing; type of sports